THE GAME THAT DAY WAS A TIGER1: IMPLICATIONS OF TIGER-HUNTING EPISODES IN SELECT AMAR CHITRA KATHA GRAPHIC HISTORICAL BIOGRAPHIES2 CONCERNING INDIAN RULERS - Guha Thakurta, Anirban (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Amar Chitra Katha, being comics and described by its makers as a route to Indian roots, has replaced the stereotypical western comic book superheroes by narrating and celebrating native heroes fetched from Indian history, mythology, legends and folk culture satisfying the needs of comic-book adventurism as well as an education achieved through entertainment. The Amar Chitra Katha ‘heroic’ graphic historical biographies were not merely intended to be a source of historical knowledge about India but also an inspiration to emulate the ideals of such heroes of native history. The present paper is a study of graphic visualizations of certain episodes related to tiger-hunting in select historical titles of Amar Chitra Katha. The paper attempts to critically examine the politics of visual aesthetics and graphic narration of historical facts related to the tiger- hunting available in such graphic historical biographies and thereby tries to diagnose whether such historical representations need to be analyzed with regard to the methodologies of representation involving postcolonial nationalist writing back or communal stereotyping and rewritten according to the pressing needs of the contemporary world concerning erosion of wildlife and anthropogenic natural disorder.